Leg venous ulcer healing process after application of membranous dressing with silver ions - Kucharzewski, M.; Wilemska-Kucharzewska, K.; Kózka, M.; Spałkowska, M. (Phlebologie, 2013)
Aim: To assess the efficiency of application of new membranous dressing with silver ions in patients with chronic venous ulceration.Methods: 58 patients were divided randomly into two groups. In group A (n=30) mean ulcer surface area was 8.52 cm2, in group B (n=28) mean wound surface area was 8.29 cm2. In group A membranous dressings with silver ions (Textus Bioactiv® by Biocell GmbH, Germany) were used. In group B hydrocolloid dressing Unna’s boot was applied. All dressings were changed every 7 days until the wound was completely healed. Changes in wound area were calculated and the speed of healing process was measured every week with healing per day index (cm2/day).Results: After 7 weeks ulcers healed in all patients of group A. Ulcers in group B healed after 16 weeks of treatment.Conclusion: On the basis of this outcome the authors concluded that application of membranous dressing with silver ions speeds up the process of treating chronic lower leg ulceration.
Keywords: Venous leg ulcer; membranous dressing; silver ions